Immunization with pentraxin 3 (PTX3) leads to anti-PTX3 antibody production and delayed lupus-like nephritis in NZB/NZW F1 mice. (November 2016) - Gatto, Mariele; Ghirardello, Anna; Luisetto, Roberto; Bassi, Nicola; Fedrigo, Marny; Valente, Marialuisa; Valentino, Sonia; Del Prete, Dorella; Punzi, Leonardo; Doria, Andrea
Abstract: Background: Anti-pentraxin 3 (PTX3) antibodies were associated with the absence of lupus glomerulonephritis in humans. Aim: To explore the effects of anti-PTX3 antibodies in New Zealand Black/White (NZB/NZW F1) mice and their inherent mechanisms of action. Materials and methods: 30 NZB/NZW F1 mice were subdivided into 3 groups of 10 mice each and subcutaneously injected with PTX3, alum and PBS (group 1), alum and PBS (group 2) or PBS alone (group 3), 3 times 3 weeks apart, before development of renal disease. Mice were followed until natural death. Histological analysis and immunohistochemistry were performed on harvested kidneys. Effects of anti-PTX3 antibodies on C1q binding to immobilized PTX3-anti-PTX3 immune complexes were evaluated in vitro using human SLE sera. Qualitative characterization of human IgG anti-PTX3 was performed. Results: Only group 1 mice developed anti-PTX3 antibodies. Anti-dsDNA and anti-C1q antibodies appeared significantly later and at lower levels in group 1 mice vs. controls (p < 0.0001). Proteinuria-free and overall survival were significantly increased in group 1 mice vs. controls (p < 0.05 and p = 0.03, respectively). Histopathological analysis showed that glomerular and tubular PTX3 staining and renal lesions were increased in controls compared with immunized mice. Addition of human SLE sera positive for anti-PTX3 antibodies to C1q and fixed PTX3 interfered with C1q binding to PTX3-anti-PTX3 immune complexes. Qualitative characterization of human IgG anti-PTX3 showed an increased proportion of IgG4. Conclusions: Anti-PTX3 antibodies delay lupus-like nephritis and prolong survival of NZB/NZW F1 mice. In vitro observations suggest anti-PTX3 antibodies may dampen complement activation via their Fc fragment, likely hindering renal inflammation. Highlights: Renal PTX3 deposition correlates with worse renal disease in lupus nephritis. Anti-PTX3 antibodies confirmed a protective role in murine lupus-like nephritis. Anti-PTX3 antibodies may hinder complement activation. IgG4 isotype may in part account for anti-PTX3 protective effect.